2012
DOI: 10.3109/17453674.2012.727079
|View full text |Cite
|
Sign up to set email alerts
|

Embalmed and fresh frozen human bones in orthopedic cadaveric studies: which bone is authentic and feasible?

Abstract: Background and purpose The most frequently used bones for mechanical testing of orthopedic and trauma devices are fresh frozen cadaveric bones, embalmed cadaveric bones, and artificial composite bones. Even today, the comparability of these different bone types has not been established.Methods We tested fresh frozen and embalmed cadaveric femora that were similar concerning age, sex, bone mineral density, and stiffness. Artificial composite femora were used as a reference group. Testing parameters were pullout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 19 publications
(45 reference statements)
2
40
0
Order By: Relevance
“…Composite femurs were also found to be good analogs to human bones regarding pull-out force of screws (Zdero et al 2007 and. On the contrary, a later study found that the pull-out force was significantly higher in composite femurs than in cadaver femurs (Topp et al 2012). …”
Section: Specimenmentioning
confidence: 97%
See 1 more Smart Citation
“…Composite femurs were also found to be good analogs to human bones regarding pull-out force of screws (Zdero et al 2007 and. On the contrary, a later study found that the pull-out force was significantly higher in composite femurs than in cadaver femurs (Topp et al 2012). …”
Section: Specimenmentioning
confidence: 97%
“…Our laboratory has traditionally used fresh frozen femurs for biomechanical experiments (Aamodt et al 2001, Wik et al 2010) and fresh frozen femurs were chosen accordingly. During the course of our study embalmed femurs were shown to provide similar mechanical properties to fresh frozen ones and could have been an alternative (Topp et al 2012). Our aim was to evaluate the implants for use in old patients with femoral neck fractures that constitute the major bulk of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 2a, the pull-out test was performed using a section of a commonly fresh frozen two years old cow tibia, which was selected to mimic the mechanical strength of the human bone [21,22]. The cortical bone screw prototype was inserted manually with a screwdriver then extracted by a universal testing machine (Instron Fast Track 8874, USA) with displacement control at a fixed rate of 0.4 mm min −1…”
Section: Mechanical and Corrosion Testingmentioning
confidence: 99%
“…20,21 However, other studies like the one by Topp et al (2012) have described similar stiffness and fracture patterns between both types of samples. Additionally, they described differences, which were not significant in screw pullout forces and axial maximum load to failure for cancellous and cortical screws.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, they described differences, which were not significant in screw pullout forces and axial maximum load to failure for cancellous and cortical screws. 22 Moreover, we evaluated differences between regions of the same embalmed samples, which diminish potential limitations caused by not utilizing fresh cadavers.…”
Section: Discussionmentioning
confidence: 99%